effectiveness of Imago Therapy Training on cognitive flexibility and parenting stress of couples with deaf children - ezzatollah ghaampour; Kourosh Amrai; Hafez Padervand; Fateme Bavazin (دانش و پژوهش در روان‌شناسی کاربردی, 2024)
Purpose: Evaluation of the effectiveness of Imago Therapy Training on cognitive flexibility and parenting stress of couples with deaf children aged 7-12 years in Khorramabad. Method: This semi-experimental study was conducted with a pre-test and post-test. The statistical population of the present study consisted of all couples with deaf children aged 7 to 12 years who had a file in the welfare center of Khorramabad in 2021. From the statistical population, 30 people were randomly selected and then this number of subjects were randomly assigned to the experimental and control groups (15 people in each group). Research data were collected using the Cognitive Flexibility Questionnaire of Dena and Van der Waals (2010) and the Barry and Jones Parent Stress Questionnaire (1995). The experimental group underwent immatotherapy training for 10 sessions of 2 hours. Data were analyzed by multivariate and univariate analysis of covariance. Results: The results of the analysis of research data showed that imagotherapy therapy has been effective in increasing cognitive flexibility and reducing the stress of parenting couples (P <0/01). The results of this study indicated the useful application of imagotherapy education approach in improving cognitive flexibility and reducing parenting stress of couples with deaf children.